2018
DOI: 10.18203/2320-1770.ijrcog20183323
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic evaluation of female infertility in low socioeconomic status

Abstract: Background: Infertility is a multidimensional health issue which is rising dramatically. The common causes include ovarian, uterine, tubal disorders, hormonal imbalance, age-related factors and lifestyle factors. The low economic strata poses a subset of problems like difficulty in seeking healthcare, treatment costs and poor compliance. Authors sought to evaluate the factors for primary and secondary infertility in women of reproductive age group who belong to low socio-economic strata using laparoscopy.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Same results were reported by Usmani who reported that patients with primary infertility presented earlier i.e. mean of 3.2 years than secondary infertility 8 .…”
Section: Discussionsupporting
confidence: 86%
“…Same results were reported by Usmani who reported that patients with primary infertility presented earlier i.e. mean of 3.2 years than secondary infertility 8 .…”
Section: Discussionsupporting
confidence: 86%
“…Usmani et al, in Rawalpindi reported 62% patients with primary infertility and 38% of patients with secondary infertility. 7 Major symptoms in our study were menstrual irregularities which was seen in 42 patients (51%) in primary infertility group and in 9 patients (40%) in secondary infertility group. The most common cause of irregular menses is PCOS which coincides with our study.…”
Section: Discussionmentioning
confidence: 53%
“…and has replaced certain old procedures like gas insufflations and even HSG in assessing the tubal patency. 4 With advances in imaging techniques such as high-resolution Trans vaginal sonography, 3D ultrasound, saline infusion sonography, HSG, need of laparoscopy for diagnosis of infertility is reduced. However, in the same sitting diagnostic laparoscopy can be converted into therapeutic procedure thus offering definitive management for the infertile couple.…”
Section: Discussionmentioning
confidence: 99%